The effect of information needs’ program on anxiety among family members in the Intensive Care Unit (ICU) - Mohd Ali, Noor Azizah (2012)
Background: Admission or hospitalization of a relative to Intensive Care Unit (ICU) can result in many psychosocial problems such as anxiety and trigger perceived needs of patient and their family members. Critical care nurses play a vital role in identifying needs and help them by providing information in this crisis period to reduce anxiety level. Objective: To determine perceived needs of family members and examine the effect of information needs’ program on anxiety level among family members of hospitalized relative in an Intensive Care Unit (ICU). Methods: A quantitative study; quasi- experimental with two non-randomised study groups, using a pre and post test design was carried out among family members whom their relative admitted to one adult general ICU. Convenience sampling of thirty- two participants from intervention and control group respectively were involved in this study. The study consists of a pre test measurement of State- Anxiety Inventory and perceived important needs using Critical Care Family Needs Inventory (CCFNI) of family members. It followed by the intervention of information needs’ program at individual basis and post test measurement of the State- Anxiety on day three was done. Data analyses were descriptive and inferential statistics of paired sample t- test, independent- t-test and Chi- square test. Results: Support subscale of CCFNI reported the mean of 45.00 (SD± 8.27) followed by Proximity; 32.25 (SD±3.16). Information subscale perceived important by the participants at the third rank with mean 27.22 (SD± 3.22), Assurance; 26.14 (SD± 1.85) and the least important subscale was Comfort; 19.04 (SD± 2.84). There was a reduction in mean score of State- Anxiety pre and post period in intervention group; from 64.81 (SD±7.39) to 58.28 (SD±9.69). Increased in mean score of State- Anxiety was observed in control group with pre mean was 64.25 (SD±6.70) and post was 67.28 (SD±8.04). The information needs’ program received by family members in intervention group has three times effective as compared to routine information given by staff nurses if any in control group. The result was statistically significant decrease in State- Anxiety scores from Pre (M= 64.81, SD± 7.39) to Post (M= 58.28, SD± 9.69, t (31) = 5.52, p < 0.001 with large effect size in intervention group. The result was not statistically significant increases in anxiety scores from Pre (M= 64.25, SD± 6.70) to post 67.28 (8.04), t (31) = -1.89, p> 0.05 (two-tailed) in control group. The mean increased in State- Anxiety score was -3.03 with small effect size. Conclusion: The findings highlighted the immediate perceived important needs by family members and the effectiveness of information needs’ program in reducing acute stage of anxiety among family members in ICU. Therefore, recommendations from the study finding need to be considered by medical and nursing personals as well as an organization. Keywords: family members, perceived needs, anxiety, intensive care unit